2020
DOI: 10.1136/bmjopen-2020-039885
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal prehabilitation as strategy for reduction of postoperative complications after cardiac surgery: a randomised controlled trial protocol

Abstract: IntroductionPrehabilitation programmes that combine exercise training, nutritional support and emotional reinforcement (multimodal prehabilitation) have demonstrated efficacy reducing postoperative complications in the context of abdominal surgery. However, such programmes have seldom been studied in cardiac surgery, one of the surgeries associated with higher postoperative morbidity and mortality. This trial will assess the feasibility and efficacy in terms of reduction of postoperative complications and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Information on the completed and ongoing EEs’ funding and conflict of interest can be found in Additional file 1 : Appendix 6. Nine EEs did not report any information, one received parts of its funding from a commercial funder [ 57 ], one from a private donor [ 46 ] and in one, it was unclear [ 68 ]. Two EEs declared a relevant conflict of interest [ 29 , 42 ], as authors were related to companies contracted to organise the prehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Information on the completed and ongoing EEs’ funding and conflict of interest can be found in Additional file 1 : Appendix 6. Nine EEs did not report any information, one received parts of its funding from a commercial funder [ 57 ], one from a private donor [ 46 ] and in one, it was unclear [ 68 ]. Two EEs declared a relevant conflict of interest [ 29 , 42 ], as authors were related to companies contracted to organise the prehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…In our opinion, home-based training, which is supervised by a dedicated physical therapist and is combined with nutritional and educational support by a dietician, could be suitable for preoperative optimization until OLT. Patients might make some progress during these weeks of training, but, most importantly, deterioration of aerobic capacity could be prevented ( 27 ) and the number of hospital admissions due to decompensated liver disease during the waiting period could be reduced ( 45 ). To the best of our knowledge, the economic burden of the implementation of a prehabilitation program in this patient population has not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this review emphasizes the need for large (multicentre) longitudinal trials that not only study the physical effects, but also focus on possible improvement of surgical outcomes after a longer duration of training during the waiting period prior to OLT. Randomizing between training and no training is, in our opinion, not ethically justifiable, because various studies ( 45 , 47 , 48 ) have shown the benefits of improved physical capacity, activity, and muscle status with surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this area of research is young with some early positive results. Ongoing trials [41,42] look to increase the amount and quality of evidence behind using prehabilitation to improve not only short-term postoperative outcomes but also long-term quality of life. Still, more work needs to be done in standardizing the definition of prehabilitation and outcomes across studies if any strong generalizations are to be made regarding this potential therapy.…”
Section: Prehabilitation Prior To Cardiac Surgerymentioning
confidence: 99%